PERTUMBUHAN DAN PRODUKSI KACANG HIJAU (Vigna radiata L.) TUMPANG SARI DENGAN JAGUNG MANIS YANG DIPERLAKUKAN PUPUK KANDANG SAPI DAN PUPUK TSP - Muhammad Antoni; Chairil Ezward; Seprido Seprido (Jurnal Sains Agro, 2021)
Green beans have a fairly high protein content and are a source of important minerals, including calcium and phosphorus. This study aims to determine the effect of cow manure and TSP on the growth and production of green beans (Vigna radiata L.) which are intercropped with sweet corn. This research was conducted in Kinali Village, Kuantan Mudik District, Kuantan Singingi Regency, from January 2020 to April 2020. The method used was factorial randomized block design (RBD), namely the first factor was the application of cow manure S which consisted of 4 treatment levels: S0 (control), S1 (0.75 kg / plot), S2, (1.5 kg / plot. ), S3 (2.25 kg / plot). The second factor is TSP (P) which consists of 4 levels of treatment: P0, (control), P1, (0.3 gr / plant), P2 (0.6 gr / plant), P3 (0.9 gr / plant ). The results showed that single cow manure had a significant effect on plant height. The best treatment was giving S3 cow dung (2.25 g / plot) with a plant height of 29.92 cm. Meanwhile, the interaction and administration of TSP alone did not have a significant effect on all observed parameters.